Effect of molybdenum addition in nickel-based catalyst on hydrogenation reaction of 2-ethyl-2-hexenal hydrogenation to 2-ethyl-hexanol - Virgana, Stephanie; Hans J, Harry; Wanadi G, Iyan; Laniwati G Subagjo, Melia; Makertihartha, IGBN (International Journal of Engineering and Technology, 2018)
The 2-ethyl-hexanol compound is much needed in the plasticizer industry as a precursor for the synthesis of bis diesters (2-ethyl hexyl) phthalate (DEHP). This compound can be synthesized by oxo reaction. One of the steps in the oxo reaction is consecutive hydrogenation reaction of the 2-ethyl-2-hexenal to 2-ethyl-hexanol. This reaction requires nickel-based catalyst as an effective step for obtaining higher and purer 2-ethyl-hexanol yields. This research aims to develop the formula and procedure of catalyst synthesized in Laboratory of Catalysis and Reaction Engineering Institut Teknologi Bandung and get a rate of the reaction. The catalysts were synthesized by co-impregnation with a nickel content of 20%-w and varied with molybdenum loading (5-20%). The support that used for these metals is alumina-phosphate (AlP2). The synthesized catalysts were tested for their activity against the 2-ethyl-2-hexenal conversion at 120Â°C, 30 bar in the fixed bed reactor and compared its performance with a commercial catalyst. The results showed the addition of molybdenum loading increases selectivity of 2-ethyl-hexanol but decrease the conversion of 2-ethyl-2-hexenal. The highest selectivity was achieved by Ni5-Mo20/AlP2 (X=31%, S=85%), but the highest conversion was achieved by Ni20/AlP2 (X=88%, S=32%). Nickel tend to play a part of breaking the C=C bond. Meanwhile, molybdenum tends to break the C=O bond. This shows that the hydrogenation of C = C bonds and the C = O bond is very depending on nickel and molybdenum metal loading.Â Â